Predictive factors for biochemical recurrence in radical prostatectomy patients - İLBEY, YUSUF ÖZLEM; Turk, Hakan; Celik, Orcun; Un, Sitki; Yoldas, Mehmet; Isoglu, Cemal Selcuk; Karabicak, Mustafa; Ergani, Batuhan; Koc, Gokhan; Zorlu, Ferruh; Ilbey, YUSUF ÖZLEM (My University, 2015)
Introduction Radical prostatectomy (RP) is considered the best treatment for the management of localized prostate cancer in patients with life expectancy over 10 years. However, a complete recovery is not guaranteed for all patients who received/underwent RP treatment. Biochemical recurrence is frequently observed during the post-operative follow-up period. The main objective in this study is to evaluate the predictive factors of biochemical recurrence in localized prostate cancer patients who underwent RP surgery